High pressure solubility of carbon dioxide (CO2) in aqueous solution of piperazine (PZ) activated N-methyldiethanolamine (MDEA) solvent for CO2 capture - Khan, S.N. (American Institute of Physics Inc., 2017)
In this study, the solubility of carbon dioxide (CO2) in the aqueous solution of piperazine (PZ) activated N-methyldiethanolamine (MDEA) was investigated. In the aqueous solution the concentrations of the N-methyldiethanolamine (MDEA) and piperazine (PZ) were kept constant at 30 wt. and 3 wt. , respectively. The solubility experiments were carried out between the temperatures ranges of 303.15 to 333.15 K. The pressure range was selected as 2-50 bar for solubility of carbon dioxide in the aqueous solution. The solubility of the CO2 is reported in terms of CO2 loading capacity of the solvent. The loading capacity of the solvent is the ratio between the numbers of moles of CO2 absorbed to the numbers of moles of solvent used. The experimental data showed that the CO2 loading increased with increase in CO2 partial pressure, while it decreased with increase in system's temperature. It was also observed from the experimental data that the higher pressure favors the absorption process while the increased temperature hinders the absorption process of CO2 capture. The loading capacity of the investigated solvent was compared with the loading capacity of the solvents reported in the literature. The investigated solvent showed better solubility in terms of loading capacity. © 2017 Author(s).